The Significance of Teacher`s Beliefs in the Learning Process - Ročāne, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays the innovative learning methods and approaches have been implemented in the learning process. Thus opportunities for the discovery of students` talents and abilities are created. Unfortunately, the lack of teachers` beliefs creates barriers in the process of discovering students` talents and abilities. Teachers` beliefs are essential in the process of introduction of the learning method-debating in the lesson. Therefore, the change of teacher`s belief is important: from only talented students can debate to each student can debate. The lack of teacher`s beliefs in the learner's ability to become a successful learner questions the expected results. The interview carried out in Liepaja Secondary School No.15 showed that the teachers' opinion is that the pedagogical belief can be changed. The experience, feedback, teacher training, as well as success stories were mentioned as teachers` beliefs influencing factors. Teacher training programs were emphasized as an essential component for strengthening teachers` beliefs, acquiring new knowledge and developing the ability to accept personal responsibility for student growth. Most of the interviewed teachers admitted that their pedagogical beliefs have been changed by the achievements of their students as well.